2013
DOI: 10.3390/ijgi2041136
|View full text |Cite
|
Sign up to set email alerts
|

Drainage Structure Datasets and Effects on LiDAR-Derived Surface Flow Modeling

Abstract: Abstract:With extraordinary resolution and accuracy, Light Detection and Ranging (LiDAR)-derived digital elevation models (DEMs) have been increasingly used for watershed analyses and modeling by hydrologists, planners and engineers. Such high-accuracy DEMs have demonstrated their effectiveness in delineating watershed and drainage patterns at fine scales in low-relief terrains. However, these high-resolution datasets are usually only available as topographic DEMs rather than hydrologic DEMs, presenting greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Research on developing an inventory of culvert datasets will allow the improved delineation of hydrologic connectivity over landscapes, as echoed in other literature (Barber & Shortridge, 2005;Li, Tang, Li, & Winter, 2013;Sofia et al, 2014). Li et al (2013) found improved connectivity through ADS locations when AGREE-based stream F I G U R E 5 Probability density functions for different DEM resolutions under a combination of depression processing methods and flow direction-accumulation algorithms. The legend in each plot follows the magnitude of the PDF peaks with the size of ADS samples within the 100 m OD threshold in parentheses.…”
Section: Effects Of Depression Processing Methodsmentioning
confidence: 88%
“…Research on developing an inventory of culvert datasets will allow the improved delineation of hydrologic connectivity over landscapes, as echoed in other literature (Barber & Shortridge, 2005;Li, Tang, Li, & Winter, 2013;Sofia et al, 2014). Li et al (2013) found improved connectivity through ADS locations when AGREE-based stream F I G U R E 5 Probability density functions for different DEM resolutions under a combination of depression processing methods and flow direction-accumulation algorithms. The legend in each plot follows the magnitude of the PDF peaks with the size of ADS samples within the 100 m OD threshold in parentheses.…”
Section: Effects Of Depression Processing Methodsmentioning
confidence: 88%
“…Incorporation of advanced LiDAR technology in wetland mapping is an efficient approach to predict the most likely inundation areas. However, we have to recognize the limitations of LiDAR data in hydrologic modeling and wetland mapping (Li et al 2013;Tang et al 2014). LiDAR data may not be accurate in wetland areas due to water body reflection and the dense vegetation coverage in wetland areas.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, R. Li et al [87] showed that drainage patterns could be determined using LiDAR-derived hydrologic DEMs by using a geospatial method. In comparison, J. Roelans et al [88] developed LiDAR Dropout Modelling by separating LiDAR data into ditch points and non-ditch points, then putting ditch points together to form a 2D polygon object to determine ditch drainage.…”
Section: Locating Road Drainage Structuresmentioning
confidence: 99%